PENGARUH DAN MANFAAT ALOKASI DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA NARAWITA - Nuri, Pitri Wulan; Suantha, Kasan K. (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
This study is based on the condition of Narawita Village, which has received a significant Village Fund Allocation over the past five years. However, the community's welfare has yet to reach the expected level. Theoretically, Village Fund Allocation should positively correlate with community welfare. Therefore, this study aims to analyze the effect of Village Fund Allocation on community welfare in Narawita Village, Cicalengka District, Bandung Regency. The research uses a quantitative method with time-series data, incorporating both secondary and primary data through documentation, surveys, interviews, and observations. Data analysis is conducted with simple linear regression using SPSS version 22. The results indicate that the Village Fund Allocation significantly affects community welfare, as evidenced by a t-test value of 13.656, supporting the hypothesis of a positive relationship between the two variables. Keywords: Accounting, Village Fund, Welfare, Community